Morning vs. evening: the role of exercise timing in enhancing fat oxidation in young men - Lan, Hao; Wu, Kaibin; Deng, Chunyun; Wang, Songtao (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to investigate the acute effects of exercise timing (morning vs. evening) on fat oxidation and energy expenditure in young men, with a focus on interactions between exercise and meal timing.MethodsEighteen male college students (23.47 ± 2.11 years) completed a randomized crossover trial under five conditions: sedentary control (SC), exercise before breakfast (EBB), exercise after breakfast (EAB), exercise before dinner (EBD), and exercise after dinner (EAD). Indirect calorimetry (COSMED K5) measured substrate utilization during exercise, post-exercise recovery (0–4 h), and the following morning. Total exercise volume (running distance) was standardized, and energy expenditure was normalized to body weight (kcal/kg).ResultsDuring the sedentary control test, participants showed similar trends in total energy expenditure. Dring exercise, the EBB group demonstrated significantly higher fat expenditure compared to EAB (P < 0.05), EBD (P < 0.01), and EAD (P < 0.01). Morning exercise overall exhibited superior fat oxidation (P < 0.01). Post-exercise (0–4 h), EBB sustained elevated fat utilization (P < 0.01 vs. EBD/EAD), while EAD showed enhanced fat oxidation the following morning (P < 0.01 vs. EAB).ConclusionThe findings suggest that exercise timing may influence temporal patterns of fat oxidation, with morning fasting potentially favoring acute lipid utilization, while evening exercise appears to correlate with delayed metabolic adjustments. Although total energy expenditure remained comparable across conditions, the observed shifts in substrate allocation imply a possible circadian-sensitive modulation of energy partitioning. These preliminary observations underscore the need for further investigation to clarify the long-term physiological relevance of such timing-dependent metabolic responses.